Introducing innovative designs for horse riding clothing for women in the Kingdom of Saudi Arabia - Alattas, Abrar Hashim; Alamodi, Hana Abdullah (Arab Journal for Sciences and Research Publishing, 2023)
This research aims to study the reality of horse-riding sportswear in the Kingdom of Saudi Arabia, and to develop designs for this sport. The research problem sprang from the desire to finds out ways towards achieving the Kingdom’s 2030 vision that supports the practice of sports by finding design solutions for sports outfits that suit women, and have comfort features that are in line with the values and culture of the Kingdom of Saudi Arabia to reflect the identity, and achieve the functional and aesthetic aspect. The research followed the descriptive analytical approach in the theoretical and survey framework, and the semi-experimental approach in creating 12 designs that include jackets, shirts, trousers, and complementary clothing for women’s horse riding. The study concluded that the most practiced type of horse-riding sport in Saudi Arabia is show jumping, and that the buying habits of the practitioners were to buy shirts and trousers more than once a year, which were of various brands based on the quality of the fabrics, and the preferred material was a mixture of cotton and spandex. The practitioners of this sport had a number of preferences and aspirations in designing clothes for this sport, including a greater multiplicity of colors, with a preference for light colors for the shirt and dark for the pants, and the need to provide innovative designs that are attractive, reflect the national identity and suit functional requirements. The direction of the opinions of specialists and riders to develop innovative designs for equestrian clothing for women that promotes national identity and maintains the specifications of sports uniforms has a statistical significance in favor of the designs developed in the research. The research concluded a set of recommendations, most notably doing more studies to find out the problems related to the design lines of women’s fashion for various sports, and providing various designs for women’s sportswear that suit their needs.